CHARACTERISTICS AND ANALYSIS OF SHALLOTS FARMING IN DOLOK SILAU SIMALUNGUN, NORTH SUMATRA - Tumpal Sipahutar; Shabil Hidayat; Moral Abadi Girsang; Lermansius Haloho; Sarman Paul Lumbantobing; Sortha Simatupang; Palmarum Nainggolan; Perdinanta Sembiring; melda S Marpaung; Delima Napitupulu (Agric, 2022)
The purpose of this study is to determine the characteristics of shallot cultivation and to understand the financial feasibility analysis in Dolok Silau Simalungun to enhance the improvement of the technology needed. Methods used in this research are survey and observation methods. Based on the assessment results, it was found that shallot farming which is planted on dry land and small scale in Sarang Padang, Dolok Silau, Simalungun has a 0,05 – 0,1 ha area. The productivity of that farming is low which averaging 5,25 tonnes/ha. The total production cost is Rp 59.598.000 with a B/C ratio of 0,59. The capital of shallot production is Rp 10.743,00 per kg. Most of the shallot production cost is absorbed by labor cost (36 %), followed by seed cost (35%). The increment of revenue can be achieved by improving productivity through the improvement of farming technologies. Technology improvements in shallot cultivation that are needed are increasing plant density, seed quality improvement, replacement of labor weeding, and the use of integrated pest and disease control. To anticipate price fluctuations, farmers need a storage technology that is a group warehouse to keep the shallot when the market price is very cheap. Institutional education needs to be strengthened for the socialization of shallot cultivation technology and innovation for the farmers.